Risk Factors for Surgical Site Infection in Patients Undergoing Breast Surgery: A Systematic Review and Meta-Analysis - Yin Liu; Zhan Yang; Dong Wang; Huan Zhang (Clinical and Experimental Obstetrics & Gynecology, 2025)
Background: Surgical site infection (SSI) following breast surgery remain a significant clinical challenge, with reported incidence rates ranging from 1% to 35%. Despite advancements in surgical techniques, SSIs contribute to prolonged hospitalization, increased mortality, and substantial healthcare costs. This research applied a quantitative systematic review and meta-analysis to identify and summarize risk factors for SSIs following breast surgery. Methods: Relevant literature from PubMed, Medline, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials published between January 1, 2004, and December 25, 2023, was searched and screened using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) procedure. The effect sizes for each identified risk factor were calculated using STATA v18 and RevMan 5.3. Heterogeneity was tested using the Q-test, and sensitivity analysis was performed using the leave-one-out method, in which one dataset was removed at a time to evaluate changes in the pooled effect sizes. A funnel plot was employed to evaluate potential publication bias. Results: 12 studies were identified, including 2412 SSI-positive and 166,794 SSI-negative cases undergoing breast surgery. 22 potential risk factors were identified, and those reported in ≥3 studies were analyzed. Mastectomy emerged as the strongest risk factor (odds ratio [OR] = 2.61, p < 0.001), followed by diabetes (OR = 2.49, p < 0.001), body mass index (BMI) ≥25 kg/m2 (OR = 2.08, p < 0.001), American Society of Anesthesiologists (ASA) score ≥3 (OR = 1.99, p < 0.001), and smoking (OR = 1.38, p < 0.001). Conclusions: Patients who underwent mastectomy demonstrated 2.61 times higher odds of developing SSI post-breast surgery (OR = 2.61). Similarly, diabetes was associated with more than twice the odds of developing SSIs (OR = 2.49), BMI ≥25 kg/m2 with twofold increase in odds (OR = 2.08), ASA score ≥3 with 99% higher odds (OR = 1.99), and smoking with a 38% increased odds (OR = 1.38). This study highlights the importance of closely monitoring surgical incisions in patients with a history of smoking, high ASA scores, or those who have undergone mastectomy. BMI and diabetes may affect each other; therefore, future studies should provide detailed reporting on the number of patients with these correlated factors. Registration: The study has been registered on https://www.crd.york.ac.uk/prospero/ (registration number: CRD42023492359).